Strengthening Digitalization of Msmes through the Ciamik Application for Alisa Khadija Diy - Tatik, Tatik; Setiani, Novi; Salsabilla, Selfira; Rahma, Indah Kartika; Febrian, Fajar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Khadija Muslim Women Entrepreneurs Association (ALISA) is a community of Muslim women entrepreneurs under the Indonesian Muslim Scholars Association (ICMI). This community service activity (PKM) aims to produce output through a simple accounting system called the